KIMYO FANINI INGLIZ TILI BILAN INTEGRATSIYALASHGAN HOLDA O‘QITISH SHAKLLARI - Ajieva, M.B.; Dauekeeva, G.U.; Umrbekova, M.U. (SCIENCE and SOCIETY, 2025)
In the modern era of globalization, interdisciplinary educational relationships are an integral part of the modern education system and serve to develop students' knowledge in several subjects simultaneously. The following article explores the prospects for teaching chemistry and English in integration. In the process of integrated classes, the most effective types of work on combining chemistry and English were considered. The integration between chemistry and English is one of the methods widely used in international education systems, allowing students not only to master chemistry in depth, but also to understand technical and scientific literature in English.
Keywords: chemistry; english language; modernization; innovation; integration; didactics; information